PENERAPAN STRATEGI PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN KEAKTIFAN DAN KETERAMPILAN MENULIS DESKRIPSI PADA SISWA KELAS X-3 MA AL-ISLAM JAMSAREN SURAKARTA - Suci Rizkiana (p-ISSN 2356-0576, 2015)
Abstract: The purpose of this research is to increase the liveliness in the process of students learning and description writing skills in a class X-3 MA Al-Islam Jamsaren Surakarta through the application of think talk write learning strategies. This study is an action research which is done in three cycles. The subject of research is Indonesian language students and teachers X- 3 MA Al-Islam Jamsaren Surakarta in the academic year 2013/2014. The source of the data in this study include: learning process, informant, and documents. Through data collection techniques: observation, interviews, document analysis, and test. Test the validity of the data using the triangular methods and data sources. Data analysis techniques used in this research is comparative descriptive technique and critical analysis. This research is able to improve the liveliness of the students in learning process and student’s skills to write a description. This liveness is reflected from the activity during (a) thinking, (b) talking, (c) writing. The percentage of students, liveness on the first cycle is 65,21%, second cycle is 82,61%, and third cycle is 95,65%. The skill improvement of students, descriptive writing is able to seen from the percentage improvement of students’ completeness on every cycle. On the first survey, students’ completeness percentage is 52,17%. First cycle is 69,57%. Second cycle is 86,97% and third cycle is 95,65%. The skill improvement of students’ descriptive writing is designated by the improvement of average score on the some aspects (a) the writing content improvement, (b) content organization, (c) vocabulary application, (d) language improvement and (e) mechanic aspects. According to the above result, it is able to concluded that the application of think talk write learning strategy is able to improve the activeness and the skill of students; descriptive writing. Keyword: think talk write learning strategy, liveliness, and descriptive writing  skills. Abstrak: Tujuan penelitian ini adalah untuk meningkatkan keaktifan dan keterampilan menulis deskripsi pada siswa kelas X-3 MA Al-Islam Jamsaren Surakarta melalui penerapan strategi pembelajaran think talk write. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam tiga siklus. Subjek penelitian adalah siswa dan guru bahasa Indonesia kelas X-3 MA Al-Islam Jamsaren Surakarta tahun ajaran 2013/2014. Sumber data dalam penelitian ini meliputi: peristiwa pembelajaran, informan, dan dokumen. Teknik pengumpulan data melalui: observasi, wawancara, tes, dan analisis dokumen. Uji validitas data menggunakan teknik triangulasi metode dan sumber data. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik deskriptif komparatif dan analisis kritis. Penerapan strategi pembelajaran think talk write terbukti dapat meningkatkan keaktifan dan keterampilan menulis deskripsi siswa. Peningkatan keaktifan siswa terefleksi dari kegiatan selama (a) berpikir (think), (b) berbicara (talk), dan (c) menulis (write). Persentase keaktifan siswa pada siklus I adalah 65,21%, siklus II 82,61%, dan siklus III 95,65%. Peningkatan keterampilan menulis deskripsi siswa dapat dilihat melalui peningkatan persentase ketuntasan siswa pada tiap siklusnya. Pada survai awal, persentase ketuntasan siswa sebesar 52,17%. Siklus I sebesar 69,57%, siklus II sebesar 86,97%, dan siklus III sebesar 95,65%. Peningkatan keterampilan menulis deskripsi siswa ditandai dengan meningkatnya nilai rata-rata aspek: (a) pengembangan isi pada tulisan, (b) organisasi isi, (c) pemanfaatan kosa kata, (d) pengembangan bahasa, dan (e) aspek mekanik. Sesuai dengan hasil di atas dapat disimpulkan bahwa penerapan strategi think talk write dapat meningkatkan keaktifan dan keterampilan menulis deskripsi siswa. Kata kunci: strategi pembelajaran think talk write, keaktifan, dan keterampilan menulis deskripsi